Handling of Public Stigma on COVID-19 in Indonesian Society - Sulistiadi, Wahyu; Rahayu, Sri; Harmani, Nanny (Kesmas, 2020)
Coronavirus disease 2019 (COVID-19) patients, their families, health workers, and cemetery officials are not only haunted by tragedies of the new coronavirus but are also stigmatized by the community. Stigma can be very detrimental to social life because it can be long-lasting without proper social measures. This qualitative study examined some cases of stigma in Indonesia. The interview was broadcast both live and online by a private television station, in April 15, 2020, and supplementary informationwas obtained from reliable news stories published by various mass media and from interviews with various groups of people. We identified the limited availability of personal protective equipment among health workers, a public lack of clear understanding regarding COVID- 19, the distortion of news by various media, and a lack of clarity among those responsible for providing education, information, and communication. The government has not acted in a sufficiently prompt mannerto prevent the spread of imported infectious diseases, resulting in local transmission and creating various stigmasamong local communities. Although the infection has already begun to spread, the government must continue toensure the correct understanding and clear mechanismsfor how to prevent COVID-19 among the public.